Conclusions. The populism-sovereignism linkage: findings, theoretical implications and a new research agenda. Issue 2 (14th March 2020) - Verzichelli, Luca
ABSTRACT: In this article, an assessment of the sovereignism- populism linkage is offered, moving from the main findings emerged in the contributions to this special issue. The sovereignism- populism linkage is seen as a challenge for comparative politics: on the one hand, the copious literature already developed, particularly in the specific field of populist parties, offers a broad set of findings and stimuli. On the other hand, the huge application (and the abuse) of the concept of populism, which has been associated to a number of very different phenomena, make the discussion on its relationships with cognate concepts more and more difficult. The article offers a first attempt to review the knowledge on the sovereignism-populism linkage, defining a new space for the empirical analysis, and refreshing the research agenda, in particular regarding some classical themes in comparative politics like the 'sustainability' of political elites and the crisis of representative institutions.